Bi-Level Preference Optimization for Retrieval-Augmented Generation (Student Abstract) - Cao, Sizhong (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Retrieval-augmented generation (RAG) is the backbone of knowledge-intensive NLP, yet its progress is hindered by a long-standing asymmetry: Generators are refined while retrievers remain static, and full end-to-end optimization is prohibitively unstable. We present BPO-RAG, a bi-level preference-learning framework that redefines the training paradigm by jointly optimizing retrieval and generation with a single supervision signal, pairwise preferences. Stage 1 (Retrieval Preference Optimization) learns to select superior evidence sets, while Stage 2 (Generation Preference Optimization) aligns answer generation with the same evidence, closing the gap between what to read and what to write. This recipe without label requires no reward model or online RL, integrates seamlessly with standard RAG pipelines, and transforms preferences into a unifying training currency. Across open-domain QA benchmarks, BPO-RAG consistently advances retrieval quality and yields more accurate, faithful answers, surpassing strong RAG baselines with remarkable stability. By coupling retrieval and generation under a unified preference framework, BPO-RAG establishes a practical and principled path toward the next generation of reliable, modular, and trustworthy knowledge-intensive language models.